Loss of the spacer loop sequence from the rrnB operon in the Escherichia coli K-12 subline that bears the relA1 mutation. - Harvey, S (1988)
A polymorphism affecting the spacer region of the rrnB rRNA operon is described. Strains from a major Escherichia coli K-12 subbranch are missing a 106-nucleotide portion of the rrnB 16S-to-23S spacer, and a 20-nucleotide sequence is found in its place. We have called this mutant operon rrnB2. The rrnB2 spacer was most probably derived from either rrnC or rrnE. This alteration of rrnB may have occurred by a recombinational exchange or by gene conversion. In the genealogy of E. coli K-12 strains, the appearance of rrnB2 is associated with the spontaneous occurrence of the first relaxed mutation, but attempts to show a selective relationship between the two mutational events have had negative results. The sequences of the rrnG and rrnC 16S-to-23S spacers have also been determined and their comparisons to the other rrn operons encoding tRNAGlu2 are presented.